Pembinaan Karakter Mandiri Dan Tanggung Jawab Siswa SD Muhammadiyah 8 Jagalan Tahun Ajaran 2016 / 2017 - Putri, Fajar Miftama Mareta, Drs. Muhroji, S.E., M.Si., M.Pd (2017)
This study aims to: 1) To describe how the independent character development planning and student responsibility SD Muhammadiyah 8 Jagalan. 2) To describe how the implementation of an independent character building and student responsibility SD Muhammadiyah 8 Jagalan. 3) To describe the character building self-evaluation and student responsibility SD Muhammadiyah 8 Jagalan. 4) To describe how the results of an independent character development and the responsibilities of SD Muhammadiyah 8 Jagalan. 5) To describe who was involved in the development of an independent character and responsibility 8 JagalanMuhammadiyah elementary school students. The research is a qualitative research with qualitative descriptive design. Informant in this research is the supervisor. Data collection techniques used were interviews, observation and documentation. The validity of research data using triangulation. Mechanical analysis includes data reduction, data presentation, drawing conclusions. The results showed that 1) Plans were made by the principal, classroom teachers, teachers of religion. Plans were made at the time the new school year. The method used in the formation of character and responsibility that is independent of lectures and assignments. 2) Implementation involves character building principals, classroom teachers, religious teachers and school committees. Implementation of an independent character building and the responsibility to do every day. Principal roles including providing direction and advice, solve problems between parents and teachers. the role of classroom teachers and religious teachers are filling an implementation guidance. The role of the committee that represents parents giving motivational coaching to children and parents. 3) Implementation of evaluation involves classroom teachers. Form of evaluation done of written tests, practice tests and questionnaires. 4) independent character and responsibilities of students after the training has been good, the children become more independent and responsibility. 5) What is involved in the development of an independent character and responsibilities of students that the principal, teachers, religious teachers, and school committees. This study therefore concluded that after a character building independence and responsibility, the better the child's character.